Analysis of Worker Posture on the Crosscut Machine Using the RULA Method in the Raw Material Division at CV. Valasindo Sentra Usaha - Indah Pratiwi; Rofi Fuad Romadhoni (Engineering Proceedings, 2025)
CV. Valasindo Sentra Usaha (VSU) is a garden furniture manufacturing company with a raw material division that has the highest number of workers and machines. The crosscut machine operators in this division reported pain in the arms, shoulders, waist, and back based on observations using the Nordic Body Map questionnaire. This study aims to analyze the ergonomics of the crosscut machine operators’ body posture using the Rapid Upper Limb Assessment (RULA) method. The analysis results showed that posture 1 had a RULA score of 6, posture 2 scored 5, and posture 3 scored 6, indicating a high ergonomic risk. Proposed improvements, such as redesigning the work desk, ergonomic chairs, and footrests, successfully reduced the RULA score to 3, showing significant improvement in the operators’ body posture.